Control interno en los proyectos de infraestructura del Gobierno Autónomo Descentralizado parroquial La Unión perteneciente al cantón Babahoyo en el periodo 2023. - Guaña Dávila, Alejandra Romina (2024)
This case study takes place in the La Unión Rural Parochial Decentralized Autonomous Government, located in Los Ríos / Babahoyo / La Unión / Abrahan Freire S/N and 9 de Octubre, under the administration of Atty. José Luis Dicao Estrada with the following RUC: 1260023000001, the general objective is to evaluate the internal control processes in the execution of infrastructure projects by the La Unión Parish Decentralized Autonomous Government (GAD), belonging to the Babahoyo canton, during the period 2023 , through analysis of budget schedules. The GAD faces various problems in the planning and execution of infrastructure projects; these challenges can include everything from budgetary limitations to coordination problems between different government entities and the local community. In addition, external factors such as political changes, adverse weather conditions or economic fluctuations can influence the successful implementation of projects. This research focuses on the evaluation of internal control in the infrastructure projects of the La Unión Parochial Decentralized Autonomous Government belonging to the Babahoyo canton in the period 2023, placing emphasis on the projected and executed income and costs. Internal control is significant within an entity as it consists of a set of standards, procedures that are developed or directed by the authorities and by the entity's personnel, with the objective of mitigating insecurities that may affect the company to the fulfillment of set objectives.